Incidence and risk factors for retinopathy of prematurity at a medical college hospital in rural Tamil Nadu, India - Elumalai, Sengodi; Kathavarayan, Rajasekaran; Govindasamy, Venkatesh (International Journal of Contemporary Pediatrics, 2020)
Background: The objective of the research was to evaluate the incidence of retinopathy of prematurity (ROP), association of prenatal and postnatal risk factors, pattern of ROP and treatment outcomes among infants admitted to neonatal intensive care unit (NICU) of tertiary care center located in Thiruvannamalai, Tamil Nadu. Methods: A retrospective study done in all infants admitted between April 2019 and March 2020 who met the criteria for ROP screening with gestational age (GA) less than or equal to 36 weeks or birth weight less than 2000 grams or with GA more than 36 weeks and birth weight more than 2000 gram with significant risk factors like intrauterine growth restriction, respiratory distress syndrome, sepsis, long term oxygen use, phototherapy, blood transfusion and maternal anemia. Treatment was offered to infants with stage 3 ROP and stage 2 in zone 2 with or without plus disease. Qualified infants were treated with argon laser photocoagulation within 72 hours of diagnosis. They were followed until the disease was successfully treated. Results: Out of total 3121 neonates, 717 neonates met the screening criteria. Incidence of ROP was found to be 33% (n=237). 46.4% (n=110) of ROP belongs to 32-36 weeks GA. 42.6% (n=101) of ROP belongs to 1500-2000 gm birth weight. Conclusions: Incidence of ROP is quite high in high risk neonates in our unit. Significant risk factors are long term oxygen use, blood transfusion and sepsis.